Configurations comparison of multidirectional matrix converter for low power application - Toosi, Saman; Misron, Norhisam; Hanamoto, Tsuyoshi; Aris, Ishak; Mohd Radzi, Mohd Amran; Yamada, Hiroaki (School of Engineering, Taylor’s University College, 2014)
Four different topologies of Multi Directional Matrix Converters (MDMC) are compared for use in low power applications. In the proposed small-scale power system the MDMC configuration with 12 bidirectional switches combined the desirable characteristics of the AC/AC conventional Matrix Converter (MC) and AC/DC single phase to single phase matrix converter. The indirect method with Space Vector Pulse Width Modulation (SVPWM) technique applied to the proposed MDMC configurations in order to control the power direction from power sources to loads. These four configurations have been simulated by MATLAB software and results are presented and discussed. Analyses and simulation results show that the MDMC with 12 bidirectional switches can run over a large input voltage and frequency range while controlling the power flow direction, compensate the fluctuating power and maintaining the excellent quality of output waveform in case of THD and DC current ripple.